Learning Physical Education, Sports and Health in Elementary Schools Based on Higher Order Thinking Skills During the Covid 19 Pandemic (Journal of Physical Education and Sports, 2022)
Physical Education, Sports and Health based on Higher Order Thinking Skill (HOTS) were carried out in elementary schools, but experienced obstacles during the Covid-19 pandemic, so research was needed to describe the conditions of the implementation of the learning. The purpose of the study was to analyze the Higher Order Thinking Skill (HOTS) based Primary School Physical Education learning during the covid 19 pandemic. This research is a qualitative descriptive study by analyzing the process, namely: 1) preparation / introduction, 2) implementation, 3) evaluation. Data collection techniques used observation, interviews, document searches, and documentation. Data analysis techniques using data collection, data reduction, data presentation, and drawing conclusions. The results of the research are HOTS-based Physical Education learning in Elementary Schools at the planning stage that teachers have made Learning Implementation Plan with sufficient categories, the HOTS-based learning process has been carried out well, the assessment stage has been carried out well. The obstacles encountered are that there are still many teachers who do not have the competence in making lesson plans. The planning stage in making lesson plans requires recommendations because it has not run optimally because they have difficulty writing character values that will be raised in learning, difficulties in using ICT/web addresses as learning resources , compiling a sample of assessment instrument items, developing scoring guidelines.